Utilization of Electric Bicycle Trainers as Learning Media to Support the Challenges of the Industrial Revolution 4.0 at SMK N 2 Probolinggo - Moh Zainul Falah; Wahyu Tri Handoko; Abdullah Iskandar Syah; Febiolola Milinia Triana; Ghasa Faraasyatul 'Alam; Fuad Indra Kusuma (CV. Creative Tugu Pena, 2024)
In the contemporary era marked by the beginning of the Fourth Industrial Revolution (4.0), the world of education faces unprecedented challenges in preparing students to face the demands of a rapidly evolving technological and industrial environment. In response, educational institutions, especially vocational schools such as SMK N 2 Probolinggo, strive to improve the competencies of their students so that they can effectively navigate and contribute to the demands of the Industrial Revolution 4.0. This research initiative stems from the awareness of the critical need to align educational practices with emerging trends and the requirements of the contemporary industrial landscape. SMK N 2 Probolinggo recognizes the importance of equipping its students with relevant skills and competencies that will enable them to thrive in an industry marked by automation, digitalization, and technological advancement. The use of electric bicycle trainers as a new learning medium signifies a proactive approach in integrating innovative pedagogical methods with real-world technology applications. By utilizing electric bicycle trainers, students are provided with hands-on experiences that simulate real-world scenarios, enabling them to develop technical proficiency, problem-solving skills, and adaptability that are essential for success in the Industrial Revolution 4.0